Pertanggungjawaban Pidana Korporasi dalam Tindak Pidana Lingkungan: Analisis Penerapan Kuhp Nasional 2023 terhadap Industri Pertambangan Mineral Dan Batubara - Pratama, Bima; Putri, Rani; Lestari, Sari (Legal Note, 2026)
Corporate criminal liability for environmental crimes in Indonesia's mining sector has undergone fundamental transformation with the enactment of Law No. 1 of 2023 on the Criminal Code (KUHP 2023), effective 2026, which explicitly recognizes corporations as criminal law subjects—a departure from the colonial-era code that solely acknowledged natural persons (Saputera, 2025; Sianipar, 2025). This research analyzes the conceptual framework of corporate criminal liability under KUHP 2023 and its application to environmental crimes in the mineral and coal mining industry, which has been implicated in widespread ecological damage including air pollution, water contamination, and degradation of ecosystems across mining-intensive regions (Winarsa, 2022). Employing normative juridical methodology with statute, conceptual, and case approaches, the study systematically examines primary legislation including KUHP 2023, Law No. 32/2009 on Environmental Protection and Management (UU PPLH), Law No. 3/2020 on Mineral and Coal Mining (UU Minerba), and Supreme Court Regulation No. 13/2016 on Corporate Criminal Procedures, alongside judicial precedents (Nurhasanah, 2021). Findings demonstrate that Articles 46-50 KUHP 2023 adopt vicarious liability doctrine, establishing three cumulative requirements for corporate liability: acts within business scope per articles of association, unlawful corporate benefit, and acceptance as corporate policy, with accountability extending to corporations, functional managers, order-givers, controlling parties, and beneficial owners (Kharisma, 2021; Saputro, 2021). Jurisprudence confirms application of polluter pays principle and strict liability in environmental enforcement, as evidenced in dumping cases involving hazardous waste disposal (Nurhasanah, 2021). However, implementation challenges persist, including structural corporate complexity obscuring liability subjects, inadequate law enforcement capacity in beneficial ownership identification, and regulatory disharmony between KUHP 2023 as lex generalis and sectoral environmental statutes as lex specialis (Winarsa, 2022). The study recommends expedited issuance of implementing regulations harmonizing KUHP 2023 with UU PPLH and UU Minerba, mandatory training for law enforcement on corporate liability doctrine, enhancement of evidentiary mechanisms including limited burden of proof reversal under UU PPLH, and establishment of proportional sanction guidelines under Article 118 KUHP 2023 considering environmental damage severity and corporate economic capacity, thereby ensuring effective deterrence and victim-centered justice in Indonesia's mining sector (Nurhasanah, 2021).